INTEGRATION OF WEATHER MONITORING-PREDICTION-WATER CONDITIONS IN CORAL CONSERVATION TOURISM AREAS - Tangian, Diane; Kapoh, Harson; Budiman, Marson James; Kamagi, Jongky W. A.; Pongtuluran, Alma K.; Polii, Bernadain D.; Kumaseh, Eunike I.; Sarapil , Costantein Imanuel; Tamarol, Joneidi; Cera, Fela Pritian; et al. (Veredas do Direito, 2026)
The coral monitoring system is designed to monitor coral growth and survival rates, integrated with weather forecasts and real-time information on marine environmental conditions at the Bahoi Likupang coral conservation site in North Minahasa Regency. The goal is to provide tourists and attraction managers with information on favorable weather and marine conditions for coral planting. Predictive analysis was performed using the Decision Tree algorithm, which demonstrated an accuracy of 85%, a precision of 0.83, and a recall of 0.87. These results demonstrate the model's ability to predict rainfall and identify patterns of relationships between environmental parameters. Field trials demonstrated that the IoT system is capable of transmitting real-time data to a web-based dashboard to display sea temperature, humidity, and weather forecasts. The integration of the predictive model and the real-time monitoring system provides an early warning function for potential environmental changes that could threaten coral reef health.